Properties of 4-fluorobenzoic acid modified zinc oxide nanoparticles by sol-gel method - Salahuddin Ahmed, Hozan (2013)
Metal oxide semiconductor has been widely studied due to it varied properties and application. Among metal oxide, ZnO semiconductor is of great interest due to the wide bandgap (3.2-3.4 eV) with hexagonal wurtzite structure. This study involves preparing ZnO by sol-gel method and the comparison of optical properties of ZnO nanoparticle at (350 and 450ºC) before and after modifying with 4-fluorobenzoic acid (4-FBA). The optical properties were studied using UV-Vis-NIR scanning spectrophotometer. FESEM image shows that the irregular spherical shape and there is variation in the surface morphology of modified and unmodified ZnO nanoparticle. The grain size increased with increasing temperature, but with addition of modifier the particle size didn’t change. The bandgap decrease with increasing temperature but recorded no changes after applying modifier. The XRD patterns of these samples are in close agreement with the JCPDS standard (No. 36-1451). It was observed that all samples were polycrystalline with hexagonal wurtzite structure with diffraction peaks oriented along the (100), (002), (101), (102), (110) and (103) planes. Fourier transforms infrared spectroscopy (FTIR) showed a band of 400-600 cm-1 corresponding to the Zn-O vibration mode.